FRAMEWORK GAMIA EDU: UM SISTEMA EDUCACIONAL GAMIFICADO, PERSONALIZADO E ADAPTADO AO ALUNO - LUSTOSA, Miriam Amanda Torres (2024)
This research deals with the personalization of gamification in platforms aimed at the educational environment, aiming at its application in higher education courses offered in the distance modality, in order to motivate and engage students. The proposal aims to develop a conceptual framework for virtual learning environments, customizing gamification, using the scale of HEXAD gamification user types, and adapting learning to the students' study style. As a methodology, it begins with a literature review, followed by the development of an instructional design, culminating in the elaboration of the proposed framework that uses machine learning to personalize the interface and user experience. The framework was validated through the implementation of an online educational system. The results indicate that gamification and personalization not only increased engagement, but also improved academic performance and satisfaction with the learning experience, pointing out that when gamification is used appropriately, with other pedagogical techniques, it overcomes certain limitations that exist in distance education. This study contributes by including a proposal for a theoretical guiding model for the implementation of personalized gamification with adaptive learning.